Surfactant-assisted galvanic synthesis and growth characteristics of copper nanowires. Issue 1 (13th November 2018) - Chang, Yu-Hsu; Lin, Tung-Jung; Wu, Yu-Chuan; Fan, Sheng-Wei; Lee, Yuan-Han; Lai, Yi-Ru
Abstract : One-dimensional copper nanowires (CuNWs) are synthesized on a large-scale using a cetyltrimethylammonium chloride-assisted galvanic replacement reaction on aluminum substrates. Abstract : One-dimensional copper nanowires (CuNWs) are synthesized on a large-scale using a cetyltrimethylammonium chloride-assisted galvanic replacement reaction on aluminum substrates. Cu(ii ) ions are reduced on the surface of aluminum foil and CuNWs with diameters of 150–300 nm are formed by fine-tuning the reaction temperature and stoichiometry of the reagents. The initial growth of the CuNWs is subjected to TEM analysis to observe the microstructure in the interface between aluminum foil and the CuNWs. The results show that copper nanoparticles form and aggregate on the AlO x H y thin layer at the initial time of the reaction following the (100) anisotropic growth of nanowires with a coating of the AlO x H y thin layer in a surfactant-assisted environment. The superior photocatalytic properties of CuNWs in the degradation of a methyl orange aqueous solution are presented in this study.